An Exploration of the Ways in Which Feelings of "Maternal Ambivalence" Affect Some Women. (April 2022) - Chapman, Emma; Gubi, Peter M.
This study explores the ways in which feelings of "maternal ambivalence" affect women. Through semistructured interviews, four women spoke about their experiences that led to ambivalent feelings about their motherhood. The data gathered from these interviews were analyzed using Interpretive Phenomenological Analysis. This research found that these women experienced a loss of independence, relationships, and confidence when they became mothers. Together, these losses felt like a loss of "self" which led to many unexpected and unwanted feelings. They were shocked and confused when they experienced feelings of resentment towards themselves, others, and their children. They also experienced unexpected feelings of boredom and anxiety in relation to mothering. However, with time and perspective, these women experienced a reemergence of "self" through their ability to begin to balance parts of "self" and accept their ambivalent feelings towards motherhood.